2017
DOI: 10.1108/ajems-10-2016-0142
|View full text |Cite
|
Sign up to set email alerts
|

Competitive advantage

Abstract: Purpose The purpose of this paper is to examine the mediating role of competitive advantage in the relationship between managerial competence and financial performance of commercial banks in Uganda. Design/methodology/approach A cross-sectional survey was employed using 22 fully licensed and operational commercial banks in Uganda. Data were analyzed using descriptive statistics, zero order correlation and hierarchical regression analyses. Further, the bootstrap method was used to test the mediation effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 43 publications
(48 reference statements)
2
47
1
3
Order By: Relevance
“…Besides that, the dynamic capabilities theory by Teece, Pisano and Shuen (1997) claims that CA developed from the dynamic capabilities of the firm can result to superior performance. In the commercial banking context, Kamukama, Kyomuhangi, Akisimire and Orobia (2017) found a partial significant mediation impact of CA in the relationship between competence and financial performance in Uganda. Saeidi et al (2015) established the mediating effect of CA in the relationship between corporate social responsibility (CSR) and financial performance.…”
Section: H7: Cloud Erp Adoption Positively Influences Organisational mentioning
confidence: 89%
“…Besides that, the dynamic capabilities theory by Teece, Pisano and Shuen (1997) claims that CA developed from the dynamic capabilities of the firm can result to superior performance. In the commercial banking context, Kamukama, Kyomuhangi, Akisimire and Orobia (2017) found a partial significant mediation impact of CA in the relationship between competence and financial performance in Uganda. Saeidi et al (2015) established the mediating effect of CA in the relationship between corporate social responsibility (CSR) and financial performance.…”
Section: H7: Cloud Erp Adoption Positively Influences Organisational mentioning
confidence: 89%
“…Managerial competencies (skills, knowledge, etc.) indirectly contribute to firms' performance via creating sustainable competitive advantage through unique resources [45]. From the upper echelon theory perspective, the top management capabilities and skills are significant drivers leading to firms' outputs [14].…”
Section: The Mediating Role Of Ramentioning
confidence: 99%
“…The connection between managerial competencies and sustainable competitive advantage remains a considerable outcome within organisational learning (Crook et al, 2008). Kamukama et al (2016), in their study, reported that managerial competencies enhanced firms' competitive advantage. Moreover, this has an indirect effect on the financial performance of commercial banks.…”
Section: Managerial Competenciesmentioning
confidence: 99%